ANALYZING THE NEEDS OF ENGLISH FOR MATHEMATICS TEACHING MATERIALS IN FACILITATING PROJECT-BASED LEARNING: STUDENTS’ AND LECTURERS’ PERSPECTIVES - Miftah Al Farhan; Iin Ariyanti (EDU-MAT: Jurnal Pendidikan Matematika, 2025)
Teaching English for Mathematics aims to develop English language skills within mathematical concepts. Currently, learning resources for English for Mathematics using the Project-Based Learning (PjBL) approach are still very limited. Therefore, this study aimed to obtain a comprehensive overview of the needs of students and lecturers for instructional materials in English for Mathematics that are designed to support the implementation of PjBL. This study employed a mixed-methods approach to collect both quantitative and qualitative data. The quantitative data consists of a needs analysis conducted through interviews with two lecturers who teach the course, while the qualitative data was gathered through a needs analysis questionnaire completed by 42 students from three different universities. The interview results revealed that lecturers expect instructional materials that thoroughly cover all stages of PjBL, including school-level mathematics content, problem-solving tasks, the eight teaching skills, interactive media, as well as control cards and assessment rubrics. The student questionnaire results indicated that although 90.7% of respondents were enthusiastic about the course, 41.8% acknowledged facing challenges, including mathematical vocabulary in English, pronunciation of mathematical symbols, and planning and delivering lessons in English. Most students (72.1%) received a video project as their course assessment. This project enhanced their confidence, speaking abilities, and comprehension. Students suggested that the course should be interactive, creative, and focused on improving their English mathematical vocabulary. Keywords: English for mathematics, project-based learning, needs analysis